Respiratory syncytial virus in influenza‐like illness cases: Epidemiology and molecular analyses of four consecutive winter seasons (2014‐2015/2017‐2018) in Lombardy (Northern Italy). Issue 12 (28th April 2020) - Pellegrinelli, Laura; Galli, Cristina; Bubba, Laura; Cereda, Danilo; Anselmi, Giovanni; Binda, Sandro; Gramegna, Maria; Pariani, Elena
Abstract: Background: Besides seasonal influenza viruses (IV), several other pathogens—including respiratory syncytial virus (RSV)—are involved in clinically undistinguished influenza‐like illnesses (ILIs). This study aimed at investigating the contribution of RSV in ILI cases in Lombardy (Northern Italy) during four consecutive winter seasons. Materials and Methods: In the framework of influenza surveillance, respiratory samples from ILI outpatients were collected from 2014‐2015 to 2017‐2018 season. IV‐negative swabs were included in the study and analyzed to detect and molecularly characterize RSV‐A and RSV‐B. Results: A total of 12.9% (135/1047) of samples were positive to RSV that was mostly detected among children ≤5 years (51/183, 27.8%) and those aged 6 to 15 years (30/158, 18.9%), whereas elderly >65 years accounted for 12% of RSV cases (15/125). The median start of RSV epidemic was in the end of November, with a peak in mid‐February and a width of nearly 4 months, almost overlapping seasonal influenza epidemic. RSV‐A and RSV‐B co‐circulated in all considered seasons, with RSV‐B predominating on RSV‐A (63.6% vs 36.4%; P < .001). Most (85.2%) RSV‐A belonged to genotype ON1 and the remaining to NA1. All RSV‐B clustered within the BA genotype. Conclusions: In this study, RSV significantly contributed to ILI cases, especially among pediatric population (<15 years), although it was detected in all age groups. RSV‐B predominated on RSV‐A, and the most recent evolved genotypes (BA and ON1, respectively) circulated. Investigating the epidemiological and molecular characteristics of RSV in ILI cases can increase baseline epidemiological information before the introduction of RSV vaccination. Highlights: RSV significantly contributed to influenza‐like illnesses (ILIs) cases, especially among pediatric population <15 years RSV‐B predominated on RSV‐A and the most recent evolved genotypes BA and ON1 circulated among ILI cases. To set up specific vaccination strategies, it is warrant increasing the current knowledge on RSV epidemiology and impact.